Comparing the impact of foot and hand reflexology on anxiety and physiological indices in colonoscopy candidates: A randomized clinical trial - Mohamad Golitaleb; Ali Safdari; Fatemeh Rafiei; Ameneh Yaghoobzadeh; Najmeh Mohamadi; Razieh Mokhtari (Contemporary Clinical Trials Communications)
Introduction and objective: Colonoscopy is a standard diagnostic procedure, yet pre-procedural anxiety remains a prevalent concern. While pharmacological interventions are available, non-pharmacological approaches such as reflexology offer a promising alternative. Despite its therapeutic potential, comparative evidence on foot and hand reflexology in this setting is limited. This study aimed to evaluate their effects on pre-colonoscopy anxiety and physiological parameters. Methods: This randomized clinical study was conducted from November 2022 to August 2023 at the Amir al-Momenin Educational and Therapeutic Center in Arak, Iran. A total of 105 patients were randomly assigned to three equal-sized groups (n = 35) using block randomization: foot reflexology, hand reflexology, and a control group. Patients in the intervention groups received a 30-min reflexology session. Anxiety levels were assessed using the Spielberger State-Trait Anxiety Inventory (STAI-Y1), a validated tool for measuring situational anxiety. Physiological indices, including systolic and diastolic blood pressure, heart rate, and arterial oxygen saturation (SpO2), were measured immediately before and after the intervention. Results: There were no significant differences in clinical outcomes among the groups at baseline (p > 0.05). However, following the intervention, the mean anxiety scores in both reflexology groups (foot reflexology: 44.39 ± 5.21; hand reflexology: 45.6 ± 4.49) were significantly lower than that of the control group (48.05 ± 4.81) (p = 0.008), as determined by one-way analysis of variance (ANOVA). The anxiety reduction was more pronounced in the foot reflexology group than the hand reflexology group, although this difference did not reach statistical significance (p > 0.05). Additionally, post-intervention assessments revealed significant differences in systolic blood pressure (foot reflexology: 123.48 ± 16.40 mmHg; hand reflexology: 122.65 ± 14.97 mmHg; control group: 132.14 ± 18.48 mmHg) and heart rate (foot reflexology: 78.60 ± 9.54 bpm; hand reflexology: 78.25 ± 11.41 bpm; control group: 85.05 ± 10.82 bpm) across the groups (p < 0.05). However, no significant differences were observed for diastolic blood pressure or arterial oxygen saturation (SPO2) between groups (p > 0.05). Conclusion: The findings of this study indicate that reflexology, particularly foot reflexology, can significantly reduce anxiety and lead to improvements in physiological parameters, such as systolic blood pressure and heart rate, in patients undergoing colonoscopy. These results highlight the potential of reflexology as an effective complementary method for managing anxiety and enhancing patient comfort during medical procedures.